Knowledge, attitudes, and practices regarding dogs and dog bites in Indigenous northern communities: A mixed methods study - Daigle, Laurence; Ravel, André; Rondenay, Yves; Simon, Audrey; Mokoush, Kabimbetas Noah; Aenishaenslin, Cécile (Frontiers in Veterinary Science, 2023)
The singular relationship developed over the years between northern Indigenous peoples and dogs has been profoundly changed through historical trauma, settlements and increased use of snowmobiles. Issues related to dogs have become increasingly complex and worrisome with the endemic presence of the rabies virus among Arctic fox populations, and given the fact that northern Indigenous peoples may have a higher risk of dog bites than the general population. This study aimed to investigate factors related to the risk of dog bites in Naskapi and Innu communities located in northern Quebec (Canada) by (1) describing the knowledge, attitudes and practices (KAP) regarding dogs and dog bites in these communities, and (2) analyzing experiences of inhabitants and health professionals with regard to dog bites and their management. A mixed methods study design that combined an observational cross-sectional survey and individual interviews was used. The survey collected data on KAP regarding dogs and dog bites among 122 respondents. Individual interviews (n=37) were then conducted with victims of dog bites, owners of dogs that have bitten a person before, and health professionals. Descriptive and inferential analysis (quantitative data) and thematic analysis (qualitative data) were performed. Results highlighted that 21 % of respondents have had a dog bite in their lifetime. Most respondents were not aware of the risk of contracting rabies following a dog bite, although rabies risk perception was associated with risk perception of dogs (Linear regression: Coefficient = 0.69, 95 % CI = 0.36-1.02). The odds of being more knowledgeable on rabies were higher (Logistic regression: OR = 2.92, 95 % CI = 1.07-7.98) among young adults. Dogs were perceived as both threats and protectors by community members. When the fear of dogs was present, it affected the quality of life of some inhabitants. There was confusion about responsibilities in the management of biting dogs, although protocols to follow after a bite were clear for health care professionals. This study revealed a lack of awareness and knowledge about dog bites and rabies risks in both communities. Results provide important knowledge for the development of interventions adapted to northern Indigenous communities.